The right to land ownership in the Black Sea and Kuban troops in the nineteenth and early twentieth centuries - Dmytro Bilyi; Vasyl Futulujchuk (Cхід)
The article deals with the peculiarities of the approach to land tenure in the tradition of the Black Sea and Kuban Cossack troops. These troops were a genetic continuation of the Zaporozhian Army and tried to preserve both their autonomy and a special economic status, which relied on the special principles of land use, which was commonly used both as stationary communities and the entire Army. The issues that are considered in the article are considered to be particularly relevant in the context of modern legislative searches for the most effective means of using Ukrainian land resources.